Comparative Study of 5 % Potassium Hydroxide Solution Versus 0.05% Tretinoin Cream for Molluscum Contagiosum in Children - Rajouria, E A; Amatya, A; Karn, D (Kathmandu University Medical Journal, 2012)
Background Molluscum contagiosum is one of the commonest cutaneous viral infections in children. All treatment modalities are associated with substantial pain, tissue destruction, and frequent recurrence. Objectives To compare the efficacy and side effects of KOH 5% solution with tretinoin 0.05% cream for the treatment of molluscum contagiosum in children. Methods Fifty patients were randomly divided into 2 groups; 25 each for 5% KOH solution and 0.05% tretinoin cream. The given medication was applied at bed time over molluscum lesions. The assessment of response and side effects were performed weekly for 4 weeks. Results At the end of 4 weeks, the mean lesion count decreased from 9.48±3.00 SD to 1.67±0.58 SD and from 8.35±2.82 SD to 2.00±1.00 SD in patients treated with 5% KOH solution and 0.05% tretinoin cream respectively. Conclusion The result of both KOH and tretinoin showed good response, well tolerated by children but between the two, KOH showed fast recovery and most lesions were resolved before 4 week. The side effects could be minimized if applied as stated above. On the other hand, tretinoin showed delayed response and even some of lesion extended beyond 4 week but the side effect were less, and hence can be used in recurrent cases. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6347 Kathmandu Univ Med J 2011;9(4):291-4